Aspects of current phonological change in Snowdrift Chipewyan - Jehn, Richard Douglas (University of Calgary, 1980)
Dramatic sound shifts are presently occurring in Snowdrift, North West Territories Chipewyan which may provide some clues to the nature of normal phonological change in language. This paper deals with the complete shift of /t/ to /k/, the loss (or voicing) of /ɬ/, the loss of morphemes which contain /ɣ/, and the reanalysis of nasalized vowels into vowel plus nasal consonant, all of which are illustrations of the type of sound change that the linguist in the field rarely expects to witness. Yes